2009
DOI: 10.1097/mpa.0b013e3181a66860
|View full text |Cite
|
Sign up to set email alerts
|

d-Dimer in Acute Pancreatitis

Abstract: Measurement of plasma levels of D-dimer on the admission is an accurate method for the identification of patients who will develop OF in the further course of AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Solely studies utilizing the Atlanta 1992 classification were considered [4]. In total, 16 studies fulfilled these criteria and were selected for the predetermination of cut-off levels [15,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. The biomarkers analyzed in these publications were interleukin-1beta (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), interleukin-10 (IL-10), tumor necrosis factor-alpha (TNF-α), monocyte chemoattractant protein-1 (MCP-1), procalcitonin and D-dimer.…”
Section: Methodsmentioning
confidence: 99%
“…Solely studies utilizing the Atlanta 1992 classification were considered [4]. In total, 16 studies fulfilled these criteria and were selected for the predetermination of cut-off levels [15,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. The biomarkers analyzed in these publications were interleukin-1beta (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), interleukin-10 (IL-10), tumor necrosis factor-alpha (TNF-α), monocyte chemoattractant protein-1 (MCP-1), procalcitonin and D-dimer.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies have shown an elevated prothrombin time in patients with AP (Radenkovic et al, 2009). However, there have been no reports of significant deviations in partial thromboplastin time (APTT) or in F1+2 levels in patients with AP.…”
Section: Coagulation and Fibrinolysis Abnormalities In Apmentioning
confidence: 99%
“…Organ dysfunction and ICU admittance occurs in approximately 38% -52% of patients with severe acute pancreatitis [5,19], and represents a worst case scenario associated with the most demanding treatment and the highest morbidity and mortality rates (21.0% -53.6%) amongst patients with acute pancreatitis [5,[20][21][22]. Ex-penses of ICU patients due to highly demanding continuous care, special equipment and therapeutic intervenetions exceed costs of patients treated in the wards by wide margins [5].…”
Section: Introductionmentioning
confidence: 99%